THE SPEECH ACT OF REQUEST IN THE CONTEXT OF INTERCULTURAL COMMUNICATION - ADAMYAN, VERA (Bulletin of Yerevan University H: Russian Philology, 2019)
The paper discusses the category of politeness on the material of the Speech Act of Request in the light of Intercultural Communication. As shown in the paper, the expression of The Speech Act of Request can show the characteristics of theparticular linguistic culture and the expression of politeness in that. In the article, in particular, Russian, Armenian and English Linguocultures are considered.
Keywords: Category of politeness, Speech Acts, Speech Act of Request, Imperative Constructions, Interrogative Constructions, Linguoculture